Mabhuku emitambo - Chigidi, Willie L. (Mambo Press, 2016)
This is a chapter in a book that deals with Shona literature. The chapter gives useful guidelines on how to read and study a play in preparation for advanced level examinations. It defines ‘mutambo’ (a play) as a literary genre, discusses, among other things, ways in which a play differs from a novel, its structure, types, and other aspects.